The Pathophysiology and Outcomes of Diabetic Patients with Coronavirus Disease 2019 (COVID-19) - Victor Perdana Kusuma; Deasy Ardiany (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Coronavirus Disease 2019 (COVID-19) is a respiratory tract infection caused by the SARS-CoV-2 virus, which was announced a pandemic by the World Health Organization (WHO) on March 11, 2020. On March 2, 2020, two confirmed cases of COVID-19 were initially reported in Indonesia. COVID-19 has been reported in 96.2 million people around the world. COVID-19 has already stolen the lives of almost 2 million individuals. Diabetes mellitus patients face an additional challenge with this disease (DM). Several studies have found a link between diabetes mellitus and COVID-19, as well as a bad prognosis for persons with DM and COVID-19. Aim of this study was to learn more about the link between diabetes and COVID-19, as well as the pathophysiology of diabetes.Methods: We searched for articles in PubMed and Google Scholar databases till February 2021, with the following keywords: “SARS-CoV-2”, “COVID-19”, “infection”, “pathogenesis”, “diabetes”Results: Diabetes Mellitus increased the severity and mortality of COVID-19 patients due to mechanisms involving inflammation and immune system activation, increased coagulation activity, oxidative stress, glucotoxicity, endoplasmic reticulum stress, renin-angiotensin-aldosterone system disorders, apoptotic mechanisms, mitochondrial dysfunction, and damage to pancreatic beta cells. COVID-19 infection can also lead to hyperglycemia and new-onset diabetes.Conlusion: Diabetes Mellitus is one of the comorbidities linked to a worse COVID-19 prognosis, according to the findings of this literature study. Furthermore, current research suggests that COVID-19 might cause hyperglycemia or new-onset diabetes, which has a poorer prognosis than COVID-19 patients with pre-existing diabetes.